Primary secretory carcinoma of thyroid with unusual features mimicking metastasis? - Joseph Teague; Allison Ciolino; Mirabelle Sajisevi (Diagnostic Pathology)
Abstract Introduction Secretory Carcinoma (SC) of the thyroid is a relatively new and often misdiagnosed cancer. Like SC of the breast and salivary gland, it is characteristically diffusely positive for S100 and Mammaglobin by immunohistochemical (IHC) staining. Methods Case report. Results A 63-year-old female presented with neck swelling and difficulty breathing. CT scan showed a large thyroid mass. Tracheal compression and deviation required stent placement and urgent radiation. Microscopic analysis showed neoplastic cells with frequent intracytoplasmic globules, including signet-ring cells. IHC stains were inconclusive to tumor type and metastasis from an occult primary was considered. However, PET-CT scan, mammography, and upper endoscopy were negative. Next-generation sequencing was performed revealing an ETV6-NTRK3 fusion favoring SC of the thyroid. Conclusions SC of the thyroid with unusual histomorphology and IHC staining may be overlooked and can mimic a metastasis. Given that a correct diagnosis critically affects prognosis and treatment, pitfalls can be avoided by utilizing molecular testing in complicated cases.